Hyphal compartmentalization and sporulation in Streptomyces require the conserved cell division protein SepX - Matthew J. Bush; Kelley A. Gallagher; Govind Chandra; Kim C. Findlay; Susan Schlimpert (Nature Communications, 2022)
Streptomyces bacteria undergo two modes of cell division: formation of cross-walls in hyphae, leading to multicellular compartments, and septation for release of unicellular spores. Here, Bush et al. identify a protein that is important for both cell division modes in Streptomyces, likely by contributing to stabilization of the divisome.